Gaping conditions of the Pectoralis minor (tenders) in commercial broilers: Prevalence, histology, and gene expression - Sunoh Che; Leonardo Susta; Pornnicha Sanpinit; Yuwares Malila; Shai Barbut (Poultry Science, 2025)
Gaping is a recently described condition that affects the Pectoralis minor (tender) muscle of broiler chickens, characterized by post-mortem separation of myofiber that leads to meat depreciation and economic losses. In this study, we aimed at understanding prevalence, morphological features, and transcriptomics signatures of this poorly understood myopathy. Between July 2022 and January 2023, a total of 5,180 chicken tenders were collected from 32 flocks across two plants in the USA, handling light (2.7 kg) and heavy (4.1 kg) birds. The prevalence of moderate and severe gaping was 24.8 % and 53.7 %, respectively. The light bird plant had a lower prevalence of moderate gaping (P < 0.001), while the heavy bird plant had a lower prevalence of severe gaping (P < 0.001). Spaghetti meat prevalence from 8,000 fillets was 46.9 % for moderate and 8.3 % for severe cases, with no significant inter-plant differences. Use of peracetic acid treatment at the poultry plants significantly increased the prevalence of severe gaping. Physical and histological features, along with gene expression, were evaluated in 120 samples representative of three gaping severity tiers. Severely gaped tenders showed greater width compared to normal and moderately gaped tenders in both light and heavy birds (P < 0.05). An increase of 1 cm in tender width was associated with a 1.99-fold increase in the odds of classification into a more severe gaping category (95 % CI: 1.15 – 3.46). Affected muscles revealed histological evidence of myodegeneration, inflammation, and lipidosis with fibrosis. For one-unit increase in the myodegeneration score, samples had a 1.75-fold increase in the odds of being classified into a more severe gaping category (95 % CI: 1.37 – 2.23). Gene expression analysis using droplet digital PCR showed differential expression of 19 genes involved in oxidative stress response, cellular signaling, muscle development, and collagen formation between weight groups and myopathy categories. Notably, 21 out of 22 differentially expressed genes showed higher expression in light birds. This study provides the comprehensive description of gaping in broiler chickens and lays a crucial benchmark for assessment of future mitigating strategies.